2022
DOI: 10.1093/abm/kaac015
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Relations Between Daily Stress and Sleep Among Black Emerging Adults

Abstract: Background Black adults experience higher levels of stress and more dysfunctional sleep patterns compared to their White peers, both of which may contribute to racial disparities in chronic health conditions. Dysfunctional sleep patterns are also more likely in emerging adults compared to other age groups. Daily stress–sleep relations in Black emerging adults are understudied. Purpose This study used ecological momentary asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…No studies reported blinding of assessors, which was expected, as most studies had observational designs. In total, 6 studies included adequate justification for the selected sample size [ 50 , 55 , 57 , 58 , 60 , 78 ], such as a power analysis [ 58 , 60 , 78 ] or another evidence supporting the argument for sample size or number of data points needed for analysis [ 50 , 55 , 57 ]. A total of 15 studies reported an attrition rate ≤20% [ 48 , 50 , 51 , 53 , 55 , 56 , 58 , 60 , 61 , 64 , 67 , 68 , 70 , 74 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No studies reported blinding of assessors, which was expected, as most studies had observational designs. In total, 6 studies included adequate justification for the selected sample size [ 50 , 55 , 57 , 58 , 60 , 78 ], such as a power analysis [ 58 , 60 , 78 ] or another evidence supporting the argument for sample size or number of data points needed for analysis [ 50 , 55 , 57 ]. A total of 15 studies reported an attrition rate ≤20% [ 48 , 50 , 51 , 53 , 55 , 56 , 58 , 60 , 61 , 64 , 67 , 68 , 70 , 74 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…In total, 43% (16/37) of the reports included measures of sleep. In these 16 reports, sleep was measured using accelerometry (10/16, 63%) [ 51 , 52 , 58 , 60 , 67 - 69 , 72 , 76 , 77 ], recall diaries or questionnaires (9/16, 56%) [ 51 , 52 , 58 , 60 , 61 , 63 , 69 , 71 , 78 ], and eEMA (3/16, 19%) [ 55 , 62 , 67 ]. Most studies included measures of both sleep duration and sleep quality [ 61 , 63 , 71 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations